Serious game on sign language - Escudeiro, Paula (2015)
The quantity of educational digital content available for the hearing impaired community is very scarce. However, due to extraordinary progress of the new technologies, remarkable opportunities to bring a better quality of life to the public in general arose. Making these opportunities available to those who endure handicap and disabilities is a core concern in today's society and a must to promote equity and inclusion. The target community addressed by our work, the hearing impaired community, has its own language, known as Sign language. The work presented in this paper consists in the development of a game to make the process of learning sign language enjoyable and interactive. In order to do this, a game was created in which the player controls a character and interacts with various objects and non-player characters with the aim of collecting several gestures from the Portuguese Sign Language. These gestures can then be represented by the character. This allows the user to visualize and learn or train the various existing gestures. To raise the interactivity and to make the game more interesting and motivating, several checkpoints were placed along the level. This will provide the players a chance to test the knowledge they have acquired so far on the checkpoints by using Kinect. A High Scores system was also created as well as a history to ensure that the game is a continuous motivating process as well as a learning process.